Relationship of Physiological Spacing and Caries in Primary Dentition: A Cross-Sectional Study - Dallakoti, Parayash; Upadhyay, Sumita; Shrestha, Rasna; Dahal, Sirjana (Journal of BP Koirala Institute of Health Sciences, 2025)
Background: Numerous factors may lead to caries in primary dentition, among them one of the important factor could be the absence of spaces between the teeth. There are not sufficient literatures available for etiologies of dental caries in primary dentition. The result of the studies performed in permanent dentition is generalised with primary dentition. So, this study aims to find out the relation of caries and absence of spacing in primary dentition. Methods: A cross-sectional observational study was conducted among patients of age three to six years in the Department of Pediatric and Preventive Dentistry, KUSMS, Dhulikhel hospital. After oral examination of the selected candidates, primate space, interdental space and intermolar spaces were recorded. Along with that, the mean of decayed, missing and filled teeth (deft) score and decayed, missing and filled surface (defs) score were recorded. Results: The mean dmft score of the study participants was 5.96 ±4.47 and the mean dmfs score was 8.72 ± 7.97. The analysis was done using Mann-Whitney U test which showed significant difference in dmft and dmfs scores between those with and without primate space and interdental space. Moreover, children without spacing presented with significantly higher dmft scores than those with the presence of any form of spacing in between teeth (p < 0.001). Conclusion: This study demonstrates that spacing in the primary dentition is significantly related with a lower dental caries experience. Hence, this justifies its role as a protective developmental feature against dental caries.